Microstructural changes in strawberry after freezing and thawing processes - Delgado, A. E. (2005)
The selection of freezing conditions is very important in order to optimize the efficiency of the freezing process and simultaneously retain the biological microstructure. Fresh strawberry and osmotically dehydrated strawberry samples were frozen and thawed using several combinations of temperatures and air velocities. Different freezing and thawing rates were used, which resulted in varying degrees of mass transport from the intercellular to extracellular domain. Scanning electron microscopy (SEM) was used to visualize the degree of structural damages caused, which depended on the crystal size and water movement. SEM showed that better preservation of the structure was obtained using high freezing or thawing rates. When high temperatures were used for thawing, the tissue damage was greater and extensive. Pre-treatment with sucrose reduced the total mass of samples to about 2.5 g/100 g in the osmotically dehydrated samples but did not affect the tissue integrity. It is concluded that the freezing–thawing conditions are responsible for the modifications observed. By using this technique it was possible to establish relationships between the tissue structure and the processing conditions.